CANDYBOTS: A New Generation of 3D‐Printed Sugar‐Based Transient Small‐Scale Robots. Issue 52 (16th November 2020) - Gervasoni, Simone; Terzopoulou, Anastasia; Franco, Carlos; Veciana, Andrea; Pedrini, Norman; Burri, Jan T.; de Marco, Carmela; Siringil, Erdem C.; Chen, Xiang‐Zhong; Nelson, Bradley J.; Puigmartí‐Luis, Josep; Pané, Salvador
Abstract: Sugars are ubiquitous in food, and are among the main sources of energy for almost all forms of life. Sugars can also form structural building blocks such as cellulose in plants. Because of their inherent degradability and biocompatibility characteristics, sugars are compelling materials for transient devices. Here, an additive manufacturing approach for the production of magnetic sugar‐based composites is introduced. First, it is shown that sugar‐based 3D architectures can be 3D printed by selective laser sintering. This method enables not only the caramelization chemistry but also the mechanical properties of the sugar architectures to be adjusted by varying the laser energy. It is also demonstrated that mixtures of sugar and magnetic particles can be processed as 3D composites. As a proof of concept, a sugar‐based millimeter‐scale helical swimmer, which is capable of corkscrew motion in a solution with a viscosity comparable to those of biological fluids, is fabricated. The millirobot quickly dissolves in water, while being manipulated through magnetic fields. The present fabrication method can pave the way to a new generation of transient sugar‐based small‐scale robots for minimally invasive procedures. Due to their rapid dissolution, sugars can be used as an intermediate step for transporting swarms of particles to specific target locations. Abstract : Sugars are among the main sources of energy and structural building blocks for almost all forms of life. Because of their degradability and biocompatibility, sugars are compelling materials in transient devices and robotics. An additive manufacturing approach for the production of 3D sugar‐based composites is introduced, which can pave the way for a new generation of transient small‐scale devices.